Efektifitas Program Rehabilitasi Berdasarkan Undang-Undang Nomor 35 Tahun 2009 Tentang Program Rehabilitasi Pencandu Narkotika Dan Psikotropika (Studi Kasus Yayasan Karunia Insani Cab Musirawas) - Handika Kartini Jefadalena; Wawan Fransico; Devi Anggreni Sy; Ahmad Fuadi (PT. AHLAL PUBLISHER NUSANTARA, 2026)
Narcotics and psychotropic abuse is a serious problem that threatens the younger generation and social stability in Indonesia. Data from the National Narcotics Agency (BNN) shows that the number of drug abusers continues to increase every year, from students, students, to productive workers. The negative impact of this coverage is not only felt by the users themselves, but also by their families, social environments, and even the state. Normative-empirical (applied) legal research is research that examines the implementation of positive legal provisions (legislation) and written documents in action (factual) in every specific legal event that occurs in society.The study aims to ensure whether the results of the application of law in legal events in concreto are in accordance with the provisions of laws and regulations.